Proceedings of the 2007 ACM/IEEE Conference on Supercomputing 2007
DOI: 10.1145/1362622.1362634
|View full text |Cite
|
Sign up to set email alerts
|

Using MPI file caching to improve parallel write performance for large-scale scientific applications

Abstract: Typical large-scale scientific applications periodically write checkpoint files to save the computational state throughout execution. Existing parallel file systems improve such write-only I/O patterns through the use of client-side file caching and write-behind strategies. In distributed environments where files are rarely accessed by more than one client concurrently, file caching has achieved significant success; however, in parallel applications where multiple clients manipulate a shared file, cache cohere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…When the first collective write operation is issued, it generates an I/O thread and the I/O thread performs the write-behind for the subsequent write operations. Client-side file caching regards each client's I/O requests are related and distributes the cache metadata and local cache pages across the processes [14], [15]. Unlike POSIX, because atomic MPI-IO operations should manage the overlapping region, such as ghost cells, Liao et al suggested process rank ordering and graph coloring [16].…”
Section: Collective I/o Improvementsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the first collective write operation is issued, it generates an I/O thread and the I/O thread performs the write-behind for the subsequent write operations. Client-side file caching regards each client's I/O requests are related and distributes the cache metadata and local cache pages across the processes [14], [15]. Unlike POSIX, because atomic MPI-IO operations should manage the overlapping region, such as ghost cells, Liao et al suggested process rank ordering and graph coloring [16].…”
Section: Collective I/o Improvementsmentioning
confidence: 99%
“…In other words, when a collective I/O operation for x · y bytes is issued, each I/O aggregator handles (x·y) 8 bytes. In the case of node 0, P 0 and P 1 handle I/O requests issued by P 0 to P 7 while P 2 and P 3 are in charge of I/O requests from P 8 to P 15 . During the data exchange phase, all I/O aggregators have to communicate with their client processes and each process uses intra-socket or inter-socket communications according to its locations.…”
Section: Collective I/o With Different Processor Affinitymentioning
confidence: 99%
“…The collective functions require participation of all processes that collectively open the file. Many collaboration strategies have been proposed and demonstrated their successes with significant performance improvements over uncoordinated I/O, such as two-phase I/O [13], [14], disk directed I/O [15], server-directed I/O [16], persistent file domain [17], [18], active buffering [19], and collaborative caching [20], [21]. However, there has not been much effort or demonstration in using MPI-IO for accessing hierarchical and irregularly distributed data sets in high performance.…”
Section: Mpi-iomentioning
confidence: 99%
“…One probing routine polls on intercommunicator to detect incoming requests from any application node, and other keeps probing on local communicator to detect the requests from peer IOD nodes. A collective MPI caching system similar to [19] [20][21] is deployed on IOD nodes to optimize the I/O requests for parallel file systems. Request detector calls corresponding MPI cache routines for performing I/O operations requested by remote application node.…”
Section: B Iodc System Designmentioning
confidence: 99%